Shame. Spectatorship Strategies in Historical Documentary Theatre - POPOVICI, Iulia (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
Taking as examples two recent theatre performances that use documentary techniques in order to deal with subjects of recent history (the largely ignored Holocaust in Bessarabia under Romanian ruling and the surveillance of private citizens, by the secret police, in Romania in the eighties), this article explores the strategies that documentary theatre employs for eliciting certain emotions among their audience. The approach takes into consideration the theories of the sociology of emotions and the theatre literature about the emotional effects of direct address in non-participatory performances, in order to develop a demonstration that for the performances given as examples, shaming/spectatorial shame response is a theatrical strategy actively chosen for its potential to overpass the conventional passiveness of the audience.